2011
DOI: 10.1109/tasc.2010.2103353
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Contact Resistance of Multi-Contact Connector in Semi-Retractable Current Lead

Abstract: Heat leakage through current leads is the dominant contributor to cryogenic heat load for various high field magnets. The semi-retractable current lead is a good option because the conductive heat leak can be eliminated after the magnet is charged. It is composed of a normal metal element and an HTS element. The normal metal element is disengaged from the HTS element through the multi-contact connector without disturbance to the insulating vacuum space and without requiring complete removal of the normal metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…To more accurately analyze the variation characteristic of contact resistance, many scholars found that changing operating conditions could also affect the contact resistance, Choi et al 13 measured the contact resistance of the connector and found that with the increase of the electrical connector’s working temperature, the size of the electrical connector increased, the contact resistance decreased. Guarino et al 14 researched the influence of thermal contact resistance of aluminum foams in forced convection.…”
Section: Introductionmentioning
confidence: 99%
“…To more accurately analyze the variation characteristic of contact resistance, many scholars found that changing operating conditions could also affect the contact resistance, Choi et al 13 measured the contact resistance of the connector and found that with the increase of the electrical connector’s working temperature, the size of the electrical connector increased, the contact resistance decreased. Guarino et al 14 researched the influence of thermal contact resistance of aluminum foams in forced convection.…”
Section: Introductionmentioning
confidence: 99%
“…The noble metal alloy electrical contact materials are widely used in aviation engine ignition contacts, high sensitivity relays, as well as micro-motor with electrical contacts, due to its excellent anti-welding, electrical conductivity, stable and low contact resistance. The study of the electric erosion phenomenon of contact materials is significant to improve its service life and reliability [1][2][3][4][5]. In recent years, many researchers have been interested in the study of arc erosion, surface morphologies and material transfer phenomenon of noble metal alloy contact materials [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%